A novel method for evaluating effects of promoters on hydrate formation. (1st May 2016) - Cai, Jing; Xu, Chun-Gang; Lin, Fu-Hua; Yu, Hai-Zhu; Li, Xiao-Sen
Abstract: Based on the SC (solute cavity) theory and the FMO (frontier molecular orbital analysis), a new method named as the SC-FMO method is established to investigate into the inherent characteristics of the hydrate formation and the effects of the hydrate promoters on the hydrate formation, and predict the hydrate structures. It is concluded from the experimental and theoretical computation results that the promoters with low frontier orbital energies, lone pairs and suitable ratios of the promoter molecular diameters to cavity diameters are favorable for moderating the hydrate formation conditions. Additionally, the water-insoluble cyclic compounds, TMS (trimethylene sulfide), CP (cyclopentane), and THT (tetrahydrothiophene) are adopted to form the binary hydrates together with methane (CH4 ). The hydrate structures are characterized by using Raman spectroscopy. The analysis results from the Raman spectra indicate that TMS, CP and THT encage into the medium 5 12 6 4 cavities of the structure II (sII) hydrates, while CH4 molecules not only occupy the small 5 12 cavities, but also compete into the medium 5 12 6 4 cavities with CP, THT or TMS molecules. The same results are predicted from the SC-FMO method. It proves that the SC-FMO is a promising method for predicting the hydrate structures and determining an excellent hydrate promoter. Highlights: A novel method SC-FMO is proposed based on SC theory and FMO analysis. Molecular parameter and orbital energy of promoter are obtained by SC-FMO. Hydrate structures are determined by Raman spectra together with SC-FMO. Results predicted by SC-FMO are consistent with experimental results.